Soil Respiration Characteristics in Three Shrublands along an Elevation Gradient in a Semiarid Loess Plateau Mountain Area. Issue 9 (15th May 2017) - Yan, Junxia; Hao, Zhong; Li, Junjian; Li, Hongian; Ding, Guangwei
ABSTRACT: Shrub is one of the major vegetation types distributed mostly in the mountainous area in China, and its vegetation carbon storage is approximately one-third of both forests and grasslands. It is essential to investigate how soil temperature (Ts ) and soil water content (Ws ) affect soil respiration (Rs ) in this ecosystem. The purpose of this study was to understand the correlations of Rs with Ts, Ws, and other factors in the shrubs. In the current study, Rs was characterized in three shrublands (hereafter, shrub 1, shrub 2, and shrub 3, respectively) located in different elevations over a 4-year period at a biweekly interval in the eastern Loess Plateau (Shanxi province) of China. Our results showed that the trend of seasonal change of Rs was controlled mainly by Ts and Ws . The measured mean Rs over 4 years was 3.64 ± 2.83 (mean ± S.D.), 2.69 ± 2.05, and 4.41 ± 3.28 μmol carbon dioxide (CO2 ) m −2 s −1 for shrubs 1, 2, and 3, respectively, exhibiting an increase trend with elevation increment. Over the season, Rs illustrated a significant change depending on the variation of Ts and Ws, with larger values appearing in summer when both Ts and Ws were high, and smaller values in winter or in summer whenever Ws was low. An exponential model (Rs = a e bTs ) fitted well the relation between Rs and Ts for shrub 3, whereas linear (Rs = a Ws + b) and power (Rs = a Ws b ) models of Rs to Ws fitted well for shrub 1. This indicated that at a lower elevation, Ws had a greater effect on Rs than that at a higher elevation. The reverse trend was true between Rs and Ts, i.e., at a higher elevation Ts had a greater effect on Rs than that at a lower elevation. The calculated Q10 values of 1.61, 3.03, and 3.73 for shrubs 1, 2, and 3 increased to 2.25, 3.63, and 4.07, respectively (when the data in low Ws conditions were excluded from the analysis), showing that Q10 increased with elevation increment. Furthermore, three two-variable models, one linear (Rs = a (Ts Ws ) + b), and two nonlinear (Rs = a Ts b Ws c and Rs = a e bTs Ws c ), were also well developed to predict the dependency of Rs on both Ts and Ws . Our research results might have important implications for the estimation of soil carbon emissions of the shrublands in this region.